2007
DOI: 10.1007/s11670-007-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study of adjuvant chemotherapy in completely resected stage III-N2 non small cell lung cancer

Abstract: Objective:To evaluate the effect of postoperative adjuvant chemotherapy on survival after complete resection of stage III-N2 non-small-cell lung cancer. Methods: From Jan. 1999 to Dec. 2003, one-hundred and fifty patients, who were diagnosed as stage III-N2 non-small cell lung cancer after operation, were randomly devided into chemotherapy group and control group. The former received four cycles of chemotherapy with NVB (25 mg/m 2 , D1, D5)/paclitaxel (175 mg/m 2 , D1) and Carboplatin (AUC=5, D1). Results: In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The full text of 23 potentially eligible articles were retrieved for detailed assessment. After layers of screening, 18 RCTs [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were included with a total of 2,158 patients randomized to receive 1 of the following 13 treatments (Fig 2A ): surgery alone (S), radiotherapy alone (R), surgery followed by adjuvant chemotherapy (SC), surgery followed by adjuvant radiotherapy (SR), neoadjuvant chemotherapy followed by surgery (CS), sequential chemoradiotherapy (CR), concurrent chemoradiotherapy (C_R), neoadjuvant sequential chemoradiotherapy followed by surgery (CRS), neoadjuvant concurrent chemoradiotherapy followed by surgery (C_RS), neoadjuvant chemotherapy followed by surgery and adjuvant chemotherapy (CSC), neoadjuvant chemotherapy followed by surgery and adjuvant radiotherapy (CSR), surgery followed by adjuvant sequential chemoradiotherapy (SCR), and surgery followed by adjuvant concurrent chemoradiotherapy (SC_R). Detailed characteristics of eligible studies are summarized in Table 1 and Supplemental Table 3.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of 23 potentially eligible articles were retrieved for detailed assessment. After layers of screening, 18 RCTs [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were included with a total of 2,158 patients randomized to receive 1 of the following 13 treatments (Fig 2A ): surgery alone (S), radiotherapy alone (R), surgery followed by adjuvant chemotherapy (SC), surgery followed by adjuvant radiotherapy (SR), neoadjuvant chemotherapy followed by surgery (CS), sequential chemoradiotherapy (CR), concurrent chemoradiotherapy (C_R), neoadjuvant sequential chemoradiotherapy followed by surgery (CRS), neoadjuvant concurrent chemoradiotherapy followed by surgery (C_RS), neoadjuvant chemotherapy followed by surgery and adjuvant chemotherapy (CSC), neoadjuvant chemotherapy followed by surgery and adjuvant radiotherapy (CSR), surgery followed by adjuvant sequential chemoradiotherapy (SCR), and surgery followed by adjuvant concurrent chemoradiotherapy (SC_R). Detailed characteristics of eligible studies are summarized in Table 1 and Supplemental Table 3.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…All 18 trials reported information on overall survival. HRs were estimated in 11 trials [25][26][27][28][29][30][31][32][33][34][35]. TrDeath was not reported in 2 studies [20,29].…”
Section: Eligible Studiesmentioning
confidence: 99%